Chitetezo Cooperative Federation Proof of Concept: Legume Value Chains, Changing Lives, Protecting Nature - Zulu, Samuel (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Community Markets for Conservation (COMACO) is a social enterprise with a mission to work with communities to secure a better life and become good stewards of their natural resources. COMACO finances enhanced climate-smart agricultural practises through the adoption of a legume-based farming system and agroforestry that increase crop yields. It also provides market opportunities for smallholder farmers by selling a variety of nature-based food products through a country-wide retail brand, "It’s Wild", and linking to carbon markets with positive conservation outcomes, including more trees, more wildlife, and healthier soils. COMACO is working with 230,000 registered farmers. Of these, 137,153 (56% women) have so far planted Gliricidia seedlings in their fields. Together, the farmers have planted a total of 37.1 million seedlings, covering 16,200 hectares of land affected by climate change.